The effect of point defects on diffusion pathway within α-Fe. (2nd April 2015) - Sakuraya, Seiji; Takahashi, Keisuke; Hashimoto, Naoyuki; Ohnuki, Somei
Abstract: The diffusion mechanism of point defects within α -Fe with a single vacancy is investigated using the density functional theory. Calculation reveals that H has a slight effect towards Fe diffusion to a vacancy. He has a strong binding with a vacancy; therefore, Fe diffusion is unlikely to happen. The diffusion of C and N from a vacancy has a high barrier. However, Fe diffusion to a vacancy decreases if the C and N diffuse from a vacancy. Thus, the effect of interstitial atoms within α -Fe with a single vacancy towards diffusion and a possible diffusion pathway is discussed.